Hubungan Pengetahuan, Paritas dan Pekerjaan Ibu Dengan Penggunaan Kontrasepsi Intra Uterine Device - Nita Anggrainy; Rizki Amalia; Hazairin Effendi (Universitas Batanghari Jambi, 2022)
The Intra Uterine Device (IUD) or spiral contraceptive is a small, elastic plastic device that is inserted into the uterus. The IUD is placed for 5 to 10 years, depending on the type or until the woman wants it removed. This study aims to determine the relationship, parity and occupation of mothers with the use of Intra Uterine Device (IUD) contraceptives in Tanjung Dalam Village, Lubuk Batang Health Center UPTD Work Area, Ogan Komering Ulu Regency in 2021. The design of this study is an analytical survey using a cross sectional study design. . The population in this study were all new and active family planning acceptors as many as 221 respondents and the number of samples as many as 69 respondents. The sampling technique used is Random Sampling. Data analysis used chi square statistical test with p value (0.05). The results of this study from 69 respondents that the research results obtained that there was a relationship between knowledge (p value = 0.002), occupation (p-value = 0.002) and parity (p-value = 0.008) with the use of intrauterine devices. The results of this study can be used as a reference to improve counseling methods for family planning acceptors, especially in the selection of IUD contraceptives.